Analysis of the Tsunami Disaster Risk Study in the Pelabuhanratu Bay Tourism Area - Moch Isya, Herdien Raka; Wibowo, Widianto Aji; Arrasyid, Riko (Universitas Pendidikan Indonesia, 2021)
The Palabuhanratu Bay area is a tourist-intensive area and the administrative center of Sukabumi Regency, so it has a very high threat of earthquake and tsunami disasters. This disaster risk assessment will form the basis of disaster management management. This research method uses a qualitative research approach with data analysis methods used are risk analysis in the form of hazard analysis, vulnerability and capacity analysis. In this study, it was found that there were 10 affected villages including Cibuntu, Cidadap, Cikakak, Citarik, Citepus, Jayanti, Palabuhanratu, Loji, Sangrawayang, and Tonjong. The tsunami risk in the affected area is classified as medium and high, meaning that the vulnerability in the 10 villages has not been efficiently balanced with regional capacity.